Pengaruh Kualitas Produk Dan Promosi Pada Kepuasan Pelanggan Kopi Kenangan Di Surabaya: Keputusan Pembelian Sebagai Variabel Mediasi - Haryadi, Helena Kadek Sri Oktadiana; Henryanto, Aria Ganna (Universitas Gorontalo, 2025)
The aim of this study was to determine the effect of product quality and promotion on Kenangan Kopi customer satisfaction through purchasing decisions as a mediating variable. The approach used is quantitative research with a questionnaire method. The questionnaire was distributed online with the help of google from media. 173 respondents were obtained with an age range of 15 to 30 years, live in Surabaya, and are consumers of Kopi Kenangan. The sampling technique used was purposive sampling. The results of distributing questionnaires were analyzed with the help of the smartPLS 3.0 application. The analysis method used is Partial Least Square (PLS), namely the outer model and inner model. The tests carried out prove that there is product quality, promotion has a positive and significant effect on purchasing decisions. In addition, product quality, promotion and purchasing decisions have a positive and significant effect on customer satisfaction. What is particularly interesting is that purchasing decisions mediate the effect of product quality and promotion on customer satisfaction. These findings encourage Kopi Kenangan companies to focus on maintaining product quality and promotion to increase customer satisfaction.